EFEK POLUTAN GARAM PADA KEGAGALANTEGANGAN ISOLATOR GANTUNG DENGANANALISIS DATA MEMAKAI PROGRAM BANTUMATLAB (The effect of Salt Pollutant on the Flashover Voltage ofSuspension Insulator Using Matlab Assistence Program to - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT This study was a laboratory study examining the effect of salt pollutant on the flashover voltage of suspension insulator using Matlab assistance program to analyze the data. The level of salt polluttant was measured based on the Equivalent Salt Deposit Density (ESDD). The background of this study was the suspension insulator used ini the tansmission lines and distribution lines having flashover voltage and also the human error in determining trendlines found in many similar studies. The aim of this study was to find out the strength of the effect of salt if Matlab program assistance was used. The implementation procedures of this study were 1). coating of insulator surface with pollutant, 2). the flashover voltage test. The result of the study showed that 1) the value of flashover voltage tended to be lower with in the increase of Equivalent Salt Deposit Density of 43.07% for ESDD increase of 0.090456 mg/an2. 3) the data analysis of the result of the study on the effect of salt pollutant in the flashover of suspension insulator using Matlab assistance progran to analyze the data was y = -258.217 X + 152.588, in fact, equal with the result using Microsoft Excel and SPSS.